How the pandemic shaped teenagers’ views on violence: exploring the complexities of post-confinement attitudes - Rodríguez, Juan Carlos; Rodríguez-Góngora, Josefina; Rodríguez-Rodríguez, José Antonio (Frontiers in Education, 2023)
Introduction Violent extremism is a complex and urgent issue that affects all sectors of society and necessitates research aimed at preventing and transforming violent behavior. Methods This study presents the findings of a questionnaire comprising 34 items administered to 1,169 teenagers from two secondary schools in Almería and Madrid, Spain, immediately following the conclusion of COVID-19 confinement measures. The primary objective of the study is to analyze teenagers’ perspectives on violent extremism and pro-violent attitudes, along with their association with various factors such as digital consumption, interpersonal relationships, and the socio-demographic circumstances of their families. Data collection involved direct interventions with the students at the participating educational institutions. Results The findings demonstrate that variables such as gender, number of siblings, and religious practice influence violent extremism, whereas nationality does not emerge as a significant factor. Additionally, the study identifies several contributing factors to the prevalence of extremist and pro-violent attitudes, and employs a moderation analysis utilizing the mother’s level of education as a moderator variable. Discussion Based on these results, the study recommends further research to enhance our understanding of the development of violent attitudes and behaviors. Additionally, it suggests implementing family and personal support programs aimed at fostering healthy adolescent development.